Polycations Stabilised by Borosulfates: [Au3Cl4][B(S2O7)2] and the One‐Dimensional Metal [Au2Cl4][B(S2O7)2](SO3). Issue 22 (23rd March 2022) - Sutorius, Stefan; van Gerven, David; Olthof, Selina; Rasche, Bertold; Bruns, Jörn
Abstract: (SO4 )‐rich silicate analogue borosulfates are able to stabilise cationic cluster‐like and chain‐like aggregates. Single crystals of [Au3 Cl4 ][B(S2 O7 )2 ] and [Au2 Cl4 ][B(S2 O7 )2 ](SO3 ) were obtained by solvothermal reaction with SO3, and the electronic properties were investigated by means of density functional theory–based calculations. [Au3 Cl4 ][B(S2 O7 )2 ] exhibits a cluster‐like cation, and the cationic gold‐chloride strands in [Au2 Cl4 ][B(S2 O7 )2 ](SO3 ) are found to resemble one‐dimensional metallic wires. This is confirmed by polarisation microscopy. Abstract : A different dimension : The borosulfates [Au3 Cl4 ][B(S2 O7 )2 ] and [Au2 Cl4 ][B(S2 O7 )2 ](SO3 ) were obtained through the reaction of AuCl3 with and in SO3 . The [B(S2 O7 )2 ] − anions serve as charge compensation for cluster‐like and chain‐like polycations. The latter are found in [Au2 Cl4 ][B(S2 O7 )2 ](SO3 ) and resemble one‐dimensional metals according to DFT‐based quantum‐chemical calculations. This is confirmed experimentally by polarisation microscopy.